Assessment of therapeutic responses to gametocytocidal drugs in Plasmodium falciparum malaria. - White, N; Ashley, E; Recht, J; Delves, M; Ruecker, A; Smithuis, F; Eziefula, A; Bousema, T; Drakeley, C; Chotivanich, K; Imwong, M; Pukrittayakamee, S; et al. (BioMed Central, 2014)
Indirect clinical measures assessing anti-malarial drug transmission-blocking activity in falciparum malaria include measurement of the duration of gametocytaemia, the rate of gametocyte clearance or the area under the gametocytaemia-time curve (AUC). These may provide useful comparative information, but they underestimate dose-response relationships for transmission-blocking activity. Following 8-aminoquinoline administration P. falciparum gametocytes are sterilized within hours, whereas clearance from blood takes days. Gametocytaemia AUC and clearance times are determined predominantly by the more numerous female gametocytes, which are generally less drug sensitive than the minority male gametocytes, whereas transmission-blocking activity and thus infectivity is determined by the more sensitive male forms. In choosing doses of transmission-blocking drugs there is no substitute yet for mosquito-feeding studies.